Cryptococcosis in Hematopoietic Stem Cell Transplant Recipients: A Rare Presentation Warranting Recognition - Carolina Firacative; Silvia Katherine Carvajal; Patricia Escandón; Jairo Lizarazo (Canadian Journal of Infectious Diseases and Medical Microbiology)
Cryptococcosis, a life-threatening mycosis caused mainly by Cryptococcus neoformans, appears to be distinctly rare in hematopoietic stem cell transplant (HSCT) recipients. When it occurs, this fungal infection is a major limitation for a successful transplant. This review comprehensively analyses 24 cases, reported in the literature, of patients with haematological malignancies including leukemias, multiple myeloma, and lymphomas, as indication for HSCT, who presented with cryptococcosis after transplantation. Of the 24 cases, 11 each occurred in patients receiving allogeneic and autologous stem cell transplants, from bone marrow, peripheral blood, and umbilical cord blood. HSCT recipients were slightly more often male, and the age of the patients ranged from 12 to 74 years. Antifungal prophylaxis was reported in most cases. Clinical manifestations of cryptococcal disease included more frequently central nervous system involvement followed by fungaemia, disseminated infection, pulmonary cryptococcosis, cerebellitis, and diarrhea. Diagnosis differed depending on the clinical presentation but habitually included cryptococcal antigen assay, India ink, and culture. Notably, not only C. neoformans but also C. albidus, C. terreus, C. laurentii, and C. adeliensis were identified as the causal species, the last two including strains resistant to fluconazole. Amphotericin B, alone or in combination, was the most common antifungal drug used for the treatment of cryptococcosis in HSCT recipients. Due to the small number of cases, it was not possible to establish if mortality rate, which was the same as survival rate, depends on the effect of the immunosuppressive regimen, the site of cryptococcal infection, and/or the antifungal therapy used to control the mycosis. Although uncommon, the recognition of cryptococcal disease in stem cell transplant is essential for a timely and adequate treatment, improved prognosis, reduced morbidity and mortality, and successful transplantation.